Mesonephric adenocarcinoma of endocervix with lobular mesonephric hyperplasia: case report - Mario Puljiz; Damir Danolić; Lucija Kostić; Ilija Alvir; Darko Tomica; Ivica Mamić; Ivana Vlastelica Munivrana; Marko Puljiz; Danko Velimir Vrdoljak; Melita Perić Balja (Acta Clinica Croatica, 2016)
Mesonephric adenocarcinoma is a rare variant of cervical adenocarcinoma. We present a case of mesonephric adenocarcinoma of endocervix with cervical and vaginal lobular mesonephric hyperplasia in a 57-year-old woman. Vaginal bleeding persisting for 12 months was the only symptom. Histopathologic findings and characteristic immunophenotype are crucial for the diagnosis. The tumor was composed of papillary formation with a central fibrovascular stroma, villoglandular and densely compact tubular structures containing intraluminal eosinophilic secretion, and coated with one or more rows of cylindrical atypical epithelial cells. There were 30 pathologic mitotic shapes found per 10 HPF. Th e tumor invaded nearly full-thickness of cervical stroma with positive lymphovascular space invasion and clear margins. The case demonstrated characteristic cytokeratin 7, vimentin and epithelial membrane antigen positivity and high Ki-67 proliferation index (60%). Estrogen receptors, progesterone receptors and carcinoembryonic antigen were negative. Intratubular lumen secretion was periodic acid-Schiff positive with periodic acid-Schiff negative carcinoma cells. Differential diagnoses include adenoma malignum, well-differentiated villoglandular adenocarcinoma, endometrioid adenocarcinoma, serous adenocarcinoma, mesonephric adenocarcinoma with a sarcomatous component, clear-cell carcinoma and mesonephric hyperplasia. Radical hysterectomy with bilateral salpingo-oophorectomy, pelvic and para-aortic lymphadenectomy was performed. Three years after the surgery, the patient remains well. There has not been any evidence of local or distant recurrence. There are no specific recommendations for the treatment of this rare disease. It remains uncertain whether surgical approach is sufficient or the treatment should include additional radio/chemotherapy.